Studi Komparasi Algoritma Decision Tree C4.5 dan K-Nearest Neighbor pada Klasifikasi Masa Studi dan Tingkat Stres Mahasiswa - Renaningtias, Nurul; Vinalti, Gushe; Putri, Tiara Eka; Purwandari, Endina Putri; Ritonga, Yusak Stainly (STMIK Banjarbaru, 2024)
This research explores the utilization of Educational Data Mining (EDM) to analyze attributes that affect students' academic performance focusing on study duration and stress levels. In this study, the performance of two classification algorithms Decision Tree C4.5 and K-Nearest Neighbor (KNN) was compared in classifying students' study duration and stress levels based on alumni data from those who graduated between 202-2023. Several variables analyzed in this dataset include gender, GPA, the number of credits taken, admission pathway, participation in organizations, and activity as an assistant. The main findings of this study indicate that gender is a significant factor in predicting students' study duration, while GPA substantially impacts students' stress levels. Regarding algorithm performance, KNN outperformed Decision Tree C4.5, achieving an accuracy rate of 71.44% for study duration classification and 64.17% for stress level classification. This research provides valuable insights for higher education institutions in formulating policies to enhance students' academic performance and well-being.Keywords: Educational Data Mining; Decision Tree C4.5; K-Nearest Neighbor; Student Study Period; Student Stress LevelÂ AbstrakPenelitian ini mengeksplorasi pemanfaatan Educational Data Mining (EDM) untuk menganalisis atribut-atribut yang memengaruhi kinerja akademik mahasiswa dengan fokus pada durasi studi dan tingkat stres. Dalam penelitian ini, kinerja dua algoritma klasifikasi yaitu Decision Tree C4.5 dan K-Nearest Neighbor dibandingkan dalam mengklasifikasikan masa studi dan tingkat stres mahasiswa berdasarkan data alumni yang lulus antara tahun 2021-2023. Variabel yang dianalisis dalam dataset ini adalah jenis kelamin, IPK, jumlah SKS yang diambil, jalur masuk, keaktifan organisasi, dan keaktifan asistensi. Temuan utama dari penelitian ini menunjukkan bahwa jenis kelamin merupakan faktor signifikan dalam memprediksi durasi studi mahasiswa, sedangkan IPK memiliki dampak substansial terhadap tingkat stres mahasiswa. Berdasarkan hasil komparasi performa algoritma, KNN lebih unggul dibandingkan Decision Tree C4.5, dengan tingkat akurasi sebesar 71,44% untuk klasifikasi durasi studi dan 64,17% untuk klasifikasi tingkat stres. Penelitian ini memberikan wawasan berharga bagi institusi pendidikan tinggi dalam merumuskan kebijakan untuk meningkatkan kinerja akademik dan kesejahteraan mahasiswa.Â